The Relationship Between Exclusive Breastfeeding and Development in Babies Aged 6-12 Months - Ismanto, Amatus Yudi; Damopoli, Melati; Sibua, Siska (Health Access Journal, 2025)
One effort to improve baby development is by providing exclusive breastfeeding. Exclusive breastfeeding is giving only breast milk without the addition of other fluids, whether formula milk, water, orange juice, or other additional foods until the baby is 6 months old. This study aims to determine the relationship between exclusive breastfeeding and the development of babies aged 6-12 months in Motongkad Selatan village. The sample is total sampling, namely 30 mothers who had breastfeeding babies with the criteria of being willing to be respondents, having babies aged 6-12 months and providing exclusive breast milk. This research is an analytical observational study, with research instruments in the form of exclusive breastfeeding questionnaires and KPSP observation sheets for children aged 6-12 months. Data were analyzed using the Chi-Square test. The results of the study showed that there was a relationship between exclusive breastfeeding and development in babies aged 6-12 months (p 0.001). It is hoped that the mother will exclusively breastfeed her baby so that the baby is healthy and develops normally